PENGARUH LINGKUNGAN, SOSIAL DAN EKONOMI TERHADAP PELAKSANAAN PROGRAM SANITASI TOTAL BERBASIS MASYARAKAT (STBM) DI KELURAHAN KOTA BARU DAN KOTA TINGGI PEKANBARU - Deddy Purnama; Rahman Karnila; Esy Maryanti (Jurnal Ilmu Lingkungan, 2018)
The Community Led Total Sanitation (CLTS) aims to change the behavior of hygiene and sanitary ware by empowering the community itself. Environmental conditions with access / facilities and sanitation, social variables with knowledge and perceptions and economic variables with income and home ownership variables influence the implementation of the CLTS program. He purpose of the study is to analyze the environment, social and economic aspects of implementation (STBM) and which ones are the most implementation. The research locations were in Kota Baru Village and Kota Tinggi Village, the study used a survey method to 66 families in Kota Baru Village and 30 households in Kota Tinggi Village by means of questionnaire investigations and observations on each selected sample. Furthermore, this study was analyzed by the SPSS P-Square statistical test program. The results of the study were Chi-Square statistical tests at the 95% confidence level of the research results with access / facilities and tourism variables in Kota Baru Subdistrict, while in Kota Tinggi Village Environmental Conditions with access / facilities and sanitation variables were not appropriate. The social conditions in Kota Baru from the variables of determining knowledge and perception are not determined, while in Kota Kelurahan Kota tinggi and economy with variables of income and home ownership in Kelurahan Kota Baru determine while in Kota Tinggi economic conditions with variable income and home ownership are not needed. The most influential factor in Kota Baru Village is that there is no knowledge while in Kota Tinggi Village.